Reapportionment and Redistricting in the West - Moncrief, Gary F. (Lexington Books, 2011)
In Reapportionment and Redistricting in the West, Gary F. Moncrief brings together some of the best-known scholars in American state and electoral politics to explore the unique processes and problems of redistricting in the western United States. These political scientists examine the specific challenges facing western states in ensuring fair and balanced political representation. Western states tend to be geographically large and experiencing rapid population growth and the chapters in this enlightening volume discuss the changing demographics in western states, paying special attention to the rise in the Latino population and the effect this has had on reapportionment and redistricting. They describe the ways in which some of these states achieve redistricting through independent redistricting commissions—a process rarely found in other regions—and they provide policy prescriptions for the future.